Effects of mycotoxin binders and a liquid immunity enhancer on the growth performance of wean-to-finish pigs - Jacela, J.Y.; DeRouchey, Joel M.; Tokach, Michael D.; Goodband, Robert D.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
A total of 1,120 pigs (PIC 337 × C22, initial BW = 16.0 lb) were used in a study to evaluate the effects of 2 commercial mycotoxin binders and a liquid immunity enhancer product on growth performance of wean-to-finish pigs. Pigs were randomly assigned to 1 of 4 treatments balanced by initial average BW within gender with 10 replicate pens per treatment. Treatments were: (1) control standard phase-fed diets based on corn and soybean meal with DDGS (20 to 35%) fed for 132 d, (2) a control diet with mycotoxin binders Biomannan fed from d 0 to 55 and T-BIND fed from d 0 to 132, (3) a control diet with Biomannan and T-BIND fed from d 0 to 132, and (4) Treatment 3 with a liquid immunity enhancer product administered through the water lines of pens continuously for 7 d every 3 wk. Both mycotoxin binders and the liquid immunity enhancer product were provided by Biotech Development Company, Inc. (Dexter, MO). The mycotoxin binder products were added in the diets at the expense of corn. Pigs from each pen were weighed as a group and feed disappearance was determined every 2 wk to determine ADG, ADFI, and F/G. Results of laboratory analysis showed that all mycotoxins tested in diet samples were below the practical quantitation limit. Overall, there were no treatment × sex interactions (P > 0.50). As expected, gender differences were noted as barrows had greater (P < 0.01) ADG and ADFI but poorer (P < 0.05) F/G than gilts. The addition of mycotoxin binders and liquid immunity enhancer product did not affect growth performance (P > 0.73) as all treatment groups had similar performance during the nursery (P > 0.28) and growing-finishing stages (P > 0.61). Under the conditions of the present study, the products tested had no effect on growth performance of wean-to-finish pigs.
Keywords: Growth; Mycotoxin binder; Swine